2021
DOI: 10.1111/dom.14473
|View full text |Cite
|
Sign up to set email alerts
|

Response to Dahl et al.: Oral semaglutide improves postprandial glucose and lipid metabolism, and delays gastric emptying, in subjects with type 2 diabetes

Abstract: Dahl et al. 1 report the first evaluation of the effect of the oral glucagon-like peptide-1 (GLP-1) receptor agonist (RA), semaglutide, on gastric emptying in type 2 diabetes. We consider that their study is compromised by substantial methodological flaws and that interpretation of the outcomes is both incorrect and misleading.In brief, in a crossover design, Dahl et al. 1 studied 15 patients with well-controlled type 2 diabetes who received oral semaglutide, escalated to a dose of 14 mg over 12 weeks and 3 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…believe that the study by Dahl et al strongly suggests that oral semaglutide has the capacity to delay gastric emptying markedly in at least some individuals with type 2 diabetes'. 1 In our article, we conclude that a 30% decrease of gastric emptying was evident in the first postprandial hour, and we were not able to detect any slowing of gastric emptying resulting from oral semaglutide in the period after the first hour. We, therefore, find it puzzling that Horowitz et al felt able to make such strong conclusions based on the reported data.…”
Section: Horowitz Et Al Conclude In Their Letter To the Editor That 'Wementioning
confidence: 54%
See 4 more Smart Citations
“…believe that the study by Dahl et al strongly suggests that oral semaglutide has the capacity to delay gastric emptying markedly in at least some individuals with type 2 diabetes'. 1 In our article, we conclude that a 30% decrease of gastric emptying was evident in the first postprandial hour, and we were not able to detect any slowing of gastric emptying resulting from oral semaglutide in the period after the first hour. We, therefore, find it puzzling that Horowitz et al felt able to make such strong conclusions based on the reported data.…”
Section: Horowitz Et Al Conclude In Their Letter To the Editor That 'Wementioning
confidence: 54%
“…It is pointed out by Horowitz et al that it would be illogical that oral semaglutide, after repeated dosing and at steady state exposure level, would only influence the first hour of postprandial gastric emptying. 1 They seem to imply that an effect on the period 0-1 hours after a meal would be an acute effect comparable with that observed from administration of other shorter-acting glucagonlike peptide-1 (GLP-1) receptor analogues. However, we do not conclude that the duration of treatment or the steady state level of exposure is related to the timing of an effect on gastric emptying.…”
Section: Horowitz Et Al Comment That Area Under the Curve (Auc) Formentioning
confidence: 95%
See 3 more Smart Citations